Associations of soil bacterial diversity and function with plant diversity in Carex tussock wetland - Li, Yan; Shi, Chuanqi; Wei, Dan; Ding, Junnan; Xu, Nan; Jin, Liang; Wang, Lei (Frontiers in Microbiology, 2023)
Some species of Carex can form tussocks, which are usually distributed in valleys and flood plains. The soil microbial community diversity and function of micro–habitats formed by tussocks are associated with plant diversity, and research on these associations can guide Carex tussock wetland restoration. In this study, we selected tussock wetlands dominated by Carex appendiculata, including natural wetlands (NW), artificially restored wetlands (ARW), and naturally restored wetlands (NRW), and investigated plant diversity. Soil samples were collected from the quadrats of each sample plot with the maximum (ma), median (me), and minimum (mi) plant Shannon index values, and high–throughput sequencing was used to analyze the bacterial community composition, diversity, and functions. The plant diversity indexes of neither ARW nor NRW significantly differed from that of NW, but the companion species in NRW were hygrophytes and mesophytes, in contrast to only hygrophytes serving as companion species in NW and ARW. The soil bacterial communities at the operational taxonomic unit level of the nine quadrats with different plant Shannon index values significantly (p < 0.01) differed. The relative abundances of the dominant phyla (Proteobacteria, Chloroflexi, and Bacteroidetes) and the dominant genera (Geobacter, Sideroxydans, and Clostridium except for unassigned genera) significantly (p < 0.05) differed under the different levels of plant diversity. The plant Shannon index, soil moisture content, total organic carbon, N, and P were significantly (p < 0.05 or p < 0.01) correlated with the bacterial Shannon index. The phylogenetic diversity of the bacterial community in NW was significantly (p < 0.0001) different from those in ARW and NRW, and that in ARW was also significantly (p < 0.05) different from that in NRW. The functional groups of bacterial communities associated with plant diversity. In the NWme, ARWme, and NRWme bacterial communities, the relative proportions of functional groups related to soil N cycle were higher, but those related to soil S and C cycles were lower. Considering the rehabilitation of both plant and microbial communities, the methods used for establishing the ARW are recommended for Carex tussock wetland restoration.